Airway management education: An update. It is high time to realize professional airway training as an art - (:unkn) unknown (ARSMB-KVBMG, 2017)
Airway training is one of the key element residents need to master during their anesthesiology teaching program. Airway-related disasters during this training might be prevented by the supervision of highly skilled airway experts as teachers. In the present day, a multimodal blended training approach helps in the planning for airway management teaching including both technical and non-technical skills. "Difficult Airway Response Team", advanced airway management rotation, case presentations to learn presenting and augmenting about clinical approaches, formalized airway training certificate based on defined competences, hands-on practices, virtual reality airway simulators, high-fidelity full-scale simulators, fresh cadavers, specific "Train the Airway Trainer Courses" resulting in certified "Airway Teachers", and ultimate delibrate practice on models and patients are cornerstones of teaching and learning airway management. Even though the working hours of the residents in the operating room are reduced due to legislation, it is still possible to provide high quality anesthesiology training to manage the airway by creating the triangle of airway management, quality improvement and patient safety. Ultimately the provision of higher quality airway training needs to be translated into improved patient safety embedded in high end healthcare organizations. © Acta Anoe sthesiologica Belgica.
Keywords: Airway management; Education; Training